A case of Rowell syndrome after a herpes simplex infection and prolonged sun exposure - Ariana Palacio; Karla Medrano Cebrian; Michael Majores; Manfred Uerlich; Erhard Bierhoff; Sonja Bonness; Uwe Reinhold (Wiley, 2024)
Abstract Rowell Syndrome is a rare entity combining erythema exudativum multiforme (EEM) and lupus erythematosus (LE). Zeitouni et al. redefined Rowell Syndrome's diagnostic criteria. Major criteria include: (1) LE (systemic, discoid or subacute cutaneous), (2) EEM‐like skin lesions and (3) speckled pattern of antinuclear antibodies. Minor criteria comprise: (1) chilblains, (2) positive anti‐SSA/Ro or anti‐SSB/La antibodies and (3) positive rheumatoid factor. The diagnosis is achieved when all major criteria and at least one minor criterion are present. Prognosis and treatment regimens are those of EEM and LE, with reported good response to oral cortisone, azathioprine, cyclosporine, dapsone, antimalarials and methotrexate. We present a case of Rowell Syndrome in a young adult after a herpes simplex type 1 infection and unprotected sun exposure, with good response to both topical corticosteroids and calcineurin‐inhibitors.